Effect of auricular acupoint buried beans combined with Nazi method of midnight-noon ebb-flow on relieving sleep disorders of nightshift nurses (耳穴埋豆联合子午流注纳子法对夜班护士睡眠障碍改善的效果评价) - LIAO Tao (廖涛); YU Shan (喻杉); WU Qianyun (伍倩云); BAO Zongming (鲍宗鸣); LIANG Jiajia (梁佳佳); CHEN Xingyue (陈兴月) (Journal of International Translational Medicine Limited, 2023)
Objective To evaluate the effect of auricular acupoint buried beans combined with Nazi method of midnight-noon ebb-flow on relieving sleep disorders in night shift nurses. Methods Eighty-four nurses with sleep disorders were randomly divided into the observation group and a control group, with 42 cases in each group. The control group received the conventional treatment of auricular acupoint buried beans, and the observation group was given the combination treatment of auricular acupoint buried beans combined with Nazi method of midnight-noon ebb-flow. Pittsburgh Sleep Quality Index (PSQI) and the Quality of Life Scale (SF-36) were used to evaluate the sleep quality and quality of life of nightshift nurses before and after the intervention. Results The scores of each dimension of PSQI in the observation group were lower than those in the control group after intervention(P＜0. 05). The SF-36 score decreased in both groups after intervention, and scores of each dimension except of physical function in the observation group were higher than those in the control group after intervention(P＜0. 05). Conclusion Both intervention methods can improve the sleep quality and quality of life of nightshift nurses, and auricular acupoint buried beans combined with Nazi method of midnight-noon ebb-flow was associated with a better treatment effect of relieving sleep disorders compared with conventional auricular acupoint buried beans. (目的 评价耳穴埋豆联合子午流注纳子法对夜班护士睡眠障碍改善的效果。方法 将84例睡眠障碍的护士随机分为观察组和对照组, 每组42例。对照组实施常规耳穴埋豆, 研究组实施耳穴埋豆联合子午流注纳子法。采用匹兹堡睡眠质量指数量表(PSQI)和生活质量量表(SF-36)评价夜班护士的睡眠质量和生活质量。结果 干预后, 观察组夜班护士PSQI量表各维度评分均低于对照组, 差异有统计学意义(P＜0. 05)。干预后, 两组SF-36量表各维度得分均较干预前升高, 且观察组SF-36量表中生活职能、躯体疼痛、一般健康状况、精力、社会职能、情感职能和精神健康维度得分高于对照组, 差异有统计学意义(P＜0. 05)。结论 两种干预方法均可提高夜班护士睡眠质量和生活质量, 耳穴埋豆联合子午流注纳子法联合对夜班护士睡眠质量的改善效果较常规耳穴埋豆更佳。)